THE VALUE OF LAND RENT ON THE CONVERSION OF COFFEE LAND INTO CITRUS FARMING LAND - Herlena Bidi Astuti; Ketut Sukiyono; Andi Irawan (AGRIBUSINESS JOURNAL, 2022)
The land is an important natural resource because land management functions to produce a valuable product and the land itself has economic value. One way to determine the value of factors of production originating from nature such as land is to use the concept of land rent. Rejang Lebong Regency is an area of citrus plantation development. the interest of farmers to plant oranges is quite high but limited land causes farmers to convert coffee fields into citrus fields. the purpose of this study was to determine the value of land rent from coffee and citrus fields on conversion land. The study was conducted in August - December 2019 in Pal VII Village, Bermani Uluraya District, Rejang Lebong Regency. census data was collected on 40 farmers. The respondent's criteria are to have a citrus crop that is already produced on the conversion land. Data were analyzed based on von Thunens's theory, namely land rent based on the market approach. The results showed that the value of land rent of citrus plants is greater than the value of the land rent of coffee plants.